THU0065 Immunomodulatory Effects of Dietary Non-Digestible Oligosaccharides in T Cell-Mediated Autoimmune Arthritis. (9th June 2015) - Rogier, R.; Ederveen, T.; Hartog, A.; Walgreen, B.; van den Bersselaar, L.; Helsen, M.; Vos, P.; Garssen, J.; Willemsen, L.; van den Berg, W.; Koenders, M.; Abdollahi-Roodsaz, S.
Abstract : Background: Accumulating evidence indicates the relevance of intestinal microbiota in shaping the immune response and supports its contribution to the development of autoimmune diseases. Prebiotic non-digestible oligosaccharides are known to selectively support growth of commensal Bifidobacteria and Lactobacilli and adjust the microbiota composition. Objectives: The aim of this study was to assess the efficacy of microbiota modulation using non-digestible oligosaccharides as a therapeutic approach for T cell-dependent autoimmune arthritis. Methods: IL-1 receptor antagonist (IL-1Ra) deficient mice spontaneously developing an autoimmune T cell-dependent arthritis were used for this study. To examine the feasibility of microbiota modulation as a therapeutic approach during established disease, IL-1Ra -/- mice which had already developed arthritis under conventional microbial status were orally fed a prebiotic diet containing short-chain galacto- and long-chain fructooligosaccharides (scGos:lcFos, 9:1). Disease progression was monitored and intestinal and systemic T cell differentiation was studied. Multiplex 454 pyrosequencing of fecal bacterial 16S rRNA was used to asses changes in composition of microbiota. Results: Oral treatment of arthritic IL-1Ra -/- mice with scGoslcFos significantly suppressed the progression of arthritis. Gene expression of T-bet and RORγt, the Th1 and Th17-related transcription factors, in lymph nodes draining the arthritic joints was significantly reduced in the group receiving the scGoslcFos diet. Furthermore, dual-energy X-ray absorptiometry scanning revealed that a prebiotic diet containing scGoslcFos significantly improved bone mineral density and tended to increase bone mineral content in arthritic IL-1Ra -/- mice. High-throughput pyrosequencing revealed a that scGoslcFos has a profound effect on relative abundance of bacteria in different taxa. The most notable alterations concerned a significant increase in Lactobacilli and a strong decrease in the genus Turicibacter . Interestingly, intestinal gene expression of the Treg-related transcription factor FoxP3 as well as anti-inflammatory cytokine IL-10 were increased with scGoslcFos. Accordingly, small intestine lamina propria lymphocytes of mice receiving the scGoslcFos diet produced significant higher levels of IL-10 upon ex vivo stimulation with PMA and ionomycin. Production of IL-4 and IFNγ also tended to be increased, while production of TNFα, IL-6 and IL-17 was not affected by the prebiotic diet. Conclusions: Our data suggest that scGoslcFos suppresses arthritis progression, potentially through induction of anti-inflammatory cytokines such as IL-10 and IL-4. Suppression of disease progression using dietary intervention with prebiotic scGoslcFos may be applicable as a therapeutic approach to suppress autoimmune arthritis. Disclosure of Interest: None declared